Peningkatan Kesiapsiagaan Remaja Melalui Pelatihan Bantuan Hidup Dasar di SMA 1 Cihaurbeuti - Irpan Ali Rahman; Yuyun Rahayu; Ima Sukmawati; Dini Nur Fauziyah; Heni Marliany; Henri Setiawan; Adi Nurapandi; Purnama Purnama (Daarul Ilmi: Jurnal Pengabdian Kepada Masyarakat, 2025)
Introduction: Adolescence is a crucial phase marked by rapid growth and development in physical, psychological, emotional, and social aspects. At this stage, preparedness to face emergency situations becomes important to ensure a safe and supportive learning environment. Emergencies such as cardiac arrest, choking, or loss of consciousness may occur unexpectedly, requiring immediate and appropriate response. However, the readiness of high school students in providing Basic Life Support (BLS) is still limited. Therefore, community service activities aimed at equipping adolescents with life-saving skills are essential to strengthen school-based emergency preparedness. Objective:The purpose of this community service program was to improve the preparedness of students at SMA 1 Cihaurbeuti through practical training in Basic Life Support (BLS). Methods: The methods used in this activity were participatory training consisting of lectures, demonstrations, and hands-on practice using manikins. Students were introduced to basic emergency management and trained to perform essential BLS procedures, including chest compressions and rescue breathing. Pre-test and post-test evaluations were conducted to measure the improvement in knowledge and skills. Results: The evaluation showed a significant improvement in students’ knowledge as indicated by the difference between the initial and final assessments. In addition, students demonstrated the ability to perform chest compressions and artificial respiration according to standard procedures. These outcomes indicate that the training effectively enhanced students’ skills and readiness in handling emergency situations. Conclusion: This community service activity was successfully implemented and resulted in increased preparedness among students at SMA 1 Cihaurbeuti in facing emergencies. The improvement in knowledge and practical skills in BLS contributes to strengthening school readiness in creating a safe and healthy learning environment.